Cytoskeleton and Morphogenesis in Brown Algae - KATSAROS, CHRISTOS (Oxford University Press, 2006)
• Background Morphogenesis on a cellular level includes processes in which cytoskeleton and cell wall expansion are strongly involved. In brown algal zygotes, microtubules (MTs) and actin filaments (AFs) participate in polarity axis fixation, cell division and tip growth. Brown algal vegetative cells lack a cortical MT cytoskeleton, and are characterized by centriole-bearing centrosomes, which function as microtubule organizing centres. • Scope Extensive electron microscope and immunofluorescence studies of MT organization in different types of brown algal cells have shown that MTs constitute a major cytoskeletal component, indispensable for cell morphogenesis. Apart from participating in mitosis and cytokinesis, they are also involved in the expression and maintenance of polarity of particular cell types. Disruption of MTs after Nocodazole treatment inhibits cell growth, causing bulging and/or bending of apical cells, thickening of the tip cell wall, and affecting the nuclear positioning. Staining of F-actin using Rhodamine-Phalloidin, revealed a rich network consisting of perinuclear, endoplasmic and cortical AFs. AFs participate in mitosis by the organization of an F-actin spindle and in cytokinesis by an F-actin disc. They are also involved in the maintenance of polarity of apical cells, as well as in lateral branch initiation. The cortical system of AFs was found related to the orientation of cellulose microfibrils (MFs), and therefore to cell wall morphogenesis. This is expressed by the coincidence in the orientation between cortical AFs and the depositing MFs. Treatment with cytochalasin B inhibits mitosis and cytokinesis, as well as tip growth of apical cells, and causes abnormal deposition of MFs. • Conclusions Both the cytoskeletal elements studied so far, i.e. MTs and AFs are implicated in brown algal cell morphogenesis, expressed in their relationship with cell wall morphogenesis, polarization, spindle organization and cytokinetic mechanism. The novelty is the role of AFs and their possible co-operation with MTs.